Measuring the Emotional well-being of secondary school students of Jorhat District. (International Journal of Psychosocial Rehabilitation, 2020)
Psychological well-being refers to the extent to which people experience positive emotions and feelings of happiness; it refers to how people evaluate their lives. The study attempted to determine the psychological well-being among secondary school students with the help of a questionnaire on a sample of forty (40) students studying in secondary schools in Jorhat District. This study mainly deals with students emotional well-being, interpersonal skills, mental health, and satisfaction of their learning outcomes. The study is conducted in two (2) secondary schools in the Jorhat district of Assam using the descriptive survey method. In this study, it was found that the majority of the students were psychologically not well, and female secondary school students were more psychologically well than the male secondary school students.